STUDI PENELUSURAN ALUMNI YANG TERSERAP DUNIA KERJA, DAN PERSEPSI ALUMNI TERHADAP KESESUAIAN KURIKULUM PRODI BIMBINGAN KONSELING ISLAM (BKI) FAKULTAS DAKWAH UIN SMH BANTEN (PENELITIAN SURVEY) - Hilda Rosida; Iwan Kosasih (UIN Sumatera Utara Medan, 2024)
An ideal educational institution is an educational institution that can carry out teaching and learning activities, provide lectures well, provide adequate standard facilities and infrastructure, professional teaching staff, a curriculum that is able to answer the challenges of the times, the creation of reliable graduates, the absorption of alumni in the world of work, the role of as well as alumni in the midst of social life. Research on the distribution of higher education alumni is absolutely necessary, this is to measure the level of success of universities, faculties and departments in providing education and preparing alumni to be able to compete in the world of work. The problems studied used the survey method. This method uses questionnaires and interviews as research tools carried out on a large population spread across several regions. The data collection techniques used are: observation, questionnaires, interviews and documentation. The total number of alumni or graduates from the 2015-2018 BKI Department at UIN Sultan Maulana Hasanuddin Banten is 319 people from four classes. Among them there are those who work, some who don't work, and some whose whereabouts are unknown. The total alumni of the Islamic Counseling Guidance Department (BKI) who have worked are 115 people out of 319 people or 79%. Alumni who don't work don't mean they can't be accepted by the job market, but rather because of strategic considerations and choices in their lives.